Sustainable improvement and evaluation of the shifting smoothness of vehicle transmission - Yongxiang Li (Nature Portfolio, 2021)
Abstract Energy savings and environmental protection are the only way for the sustainable development of the automotive industry. The poor shifting performance of automobile transmission may reduce the driver's driving pleasure and make the driver feel tired. In addition, improper shifting would also increase fuel consumption. Therefore, in view of the importance of improving the shift performance of vehicle transmission, GSA testing technology was employed for the existing shift quality problems of commercial vehicles to continuously realize high shifting efficiency and low fuel consumption. Through the establishment of subjective and objective evaluation criteria of the experimentally determined shift performance of commercial vehicles, a reliable theoretical basis is provided for product optimization design and shift performance evaluation. As a result, the shift control strategy and optimization matching measures are formulated to ensure that the power, smoothness and transmission of the whole vehicle system meet the technical requirements and finally achieve a rapid and stable gearshift. Thus, this work unveils the high potential of improving the shift performance and quality of the whole vehicle and is expected to have an impact on reducing fuel consumption and emissions in the relevant automotive industry, contributing to the establishment of a more sustainable society.